USING STORYTELLING AS A STRATEGY TO TEACH INDONESIAN TO THE FIRST GRADE STUDENTS OF CHRISTMAS ELEMENTARY SCHOOL KUPANG IN ACADEMIC YEAR 2022/2023 - BENU, MEGA NORMAWATI; BUSTAN, FRANSISKUS; HAAN, JOHN WEM (Postgraduate School, Universitas Nusa Cendana, 2023)
The world of education in Kupang is improving to implement an education system that is considered capable of meeting global challenges. Starting from the design of curriculum, the application of English in daily life, to the learning methods adapted to the implementation of primary and secondary education in developed countries. Christian Montessori School (CHRISTMAS) is one of the International schools in Kupang. The use of English in daily life both in class and during recess at school from kindergarten, elementary school to junior high school is very helpful for children facing global challenges. The aims of this research are formulated as follows (i) to identify strengths and weaknesses of using storytelling as a strategy to teach Indonesian of CHRISTMAS elementary school Kupang in academic year 2022/2023.(ii) to identify opportunities and threats of using storytelling as a strategy to teach Indonesian of CHRISTMAS elementary school Kupang in academic year 2022/2023. The subjects of this study were the first grade students of CHRISTMAS elementary school Kupang. The Researcher collects data by observing, interviewing, and analyzing documents. After that, the researcher did a reflection of the teaching strategy. Based on the result of this research, the researcher found that there are some strengths, weaknesses, opportunities, and threats to using storytelling as a strategy to teach Indonesian to the first grade students of CHRISTMAS elementary school Kupang. So the result of this study was applied by students filling out the answer sheets first to express their main ideas. Students will learn the lesson using English in the classroom. Keywords: storytelling, elementary school, first grade students, strengths and weaknesses, opportunity and threats.